Evaluation of sleep quality and nutritional status of patients with frequent ventricular premature complexes (Annals of Medical Research, 2021)
Aim: Rhythm disturbances in the heart significantly affect the quality of life of the patients. The aim of this study was to investigate the effect of ventricular premature complexes (VPC) on sleep quality and nutritional status.Material and Methods: This study was conducted on 50 patients with palpitations who were referred to the cardiology outpatient clinic and had more than 10,000 VPC per day as a result of a 24-hour holter, and 50 patients who presented with palpitations but had less than 10,000 VPC in the holter. Demographic characteristics, nutritional status, sleep quality and some anthropometric measurements of the patients were evaluated using a questionnaire. Food consumption record was taken to determine daily energy and macro nutrient intake of individuals. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality.Results: PSQI scores indicating decreased sleep quality were found to be high in the VPC group (p0.001). Energy consumption (p = 0.004) and carbohydrate consumption (p0.001) were significantly higher in the VPC group. Saturated fatty acid consumption was high (p0.001) and polyunsaturated fatty acid consumption was low in the VPC group (p0.001).There was significant positive correlation found between VPC count and PSQI scores (p0.001, r = 0.788).Conclusion: It was clearly observed that the frequency of VPC decreases sleep quality and leads to imbalances in individuals’ nutritional status. Therefore, in addition to the medical treatment of rhythm disorder, individuals should be given training to improve sleep quality and nutritional status by a multidisciplinary team (such as doctors, dietitians, psychologists).
Keywords: Ventricular premature complexes; nutritional status; sleep quality